ANCA-negative small vessel vasculitis: a case report in a 41-year-old male - Oceguera, Valeria Contreras; Campollo, Maria de Lourdes Ochoa (International Journal of Research in Dermatology, 2025)
Non-leukocytoclastic small vessel vasculitis is an uncommon inflammatory disorder characterized by vascular wall damage without evidence of leukocytoclasia. We present the case of a 41-year-old male with ANCA-negative small vessel vasculitis limited to the skin. The patient developed pruritic violaceous macules on the lower limbs and showed histopathologic findings of small-vessel vasculitis with neutrophilic infiltrate. Treatment with systemic corticosteroids resulted in favorable clinical evolution without recurrence. This case highlights the importance of comprehensive clinical assessment and individualized management in cutaneous vasculitis, emphasizing clinical judgment over immunological markers.